Effects of surface ligands on energetic disorder and charge transport of P3HT:CdSe hybrid solar cells. Issue 6 (30th January 2015) - Li, Lijun; Greaney, Matthew J.; Li, Kejia; Sachdeva, Angad; Brutchey, Richard L.; Campbell, Joe C.
<x xml:space="preserve">Abstract</x> In this work, the effects of surface ligands of cadmium selenide (CdSe) nanocrystals on energetic disorder and charge transport of poly (3‐hexylthiophene‐2, 5‐diyl):cadmium selenide (P3HT:CdSe) hybrid bulk heterojunction solar cells were studied. Photo‐induced current transient spectroscopy (PICTS) was employed to quantitatively characterize the trap state energies in P3HT:CdSe hybrid solar cells from pyridine (Py) and tert‐butylthiol (tBT) treated CdSe nanocrystals. A data processing workflow to extract the trap emission spectra was implemented in the form of solving an inverse problem with regularization techniques. We observed significant differences in the trap state distribution in P3HT:CdSe(tBT) compared to P3HT:CdSe(Py) solar cells, and we found that devices based on P3HT:CdSe(Py) had deeper level trap states. Additionally, transient photoconductivity measurements were performed on P3HT:CdSe solar cells for the purpose of examining the effects of ligands on charge transport. The results were self‐consistent with PICTS analysis in that P3HT:CdSe(tBT) devices exhibited a greater than three‐fold enhancement in carrier mobility relative to P3HT:CdSe(Py) devices, which we attributed to a decreased depth of trap states.